PUSAT PENAMPUNGAN HEWAN DI KOTA PONTIANAK - Meyliany, Meyliany; Alhamdani, Muhammad Ridha; Andi, Uray Fery (JMARS: Jurnal Mosaik Arsitektur, 2025)
The surging number of pet ownerships has mirrored the trajectory of the growth of human population, ultimately contributing to the commercialization of pets. Practices carried by breeders or pet shops often neglect animal welfare. The lack of public education and awareness about pet ownership"™s responsibilities eventually has led to higher abandonment rates of animals, particularly for cats and dogs frequently found roaming unsupervised in urban environments. Moreover, ineffective animal population control policies, combined with limited shelter capacity and operational constraints, further exacerbate the issue of stray animal overpopulation. In Pontianak City, there is currently no adequate and integrated animal shelter facility. Therefore, this design aims to provide a space that not only houses stray animals, but also cares for, trains, educates, and provides a means of interaction between animals and humans. The design method applied refers to Snyder & Catanese's 5 design steps, which include the initiation, preparation, proposal submission, evaluation stages, and action.. The design approach applied focuses on accommodating the natural behaviour of animals with the theme of Freedom & Engage, which is translated into the building's form, circulation, and functions. The design outcome is an animal shelter facility which relevanst to current challenges and needs in field.